2022
DOI: 10.7759/cureus.21264
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Low Serum Vitamin D Level and Early Dental Implant Failure: A Systematic Review

Abstract: The variety in shape and type of dental implants in the present time is considered one of the most successful evolutions in dentistry. This facilitates dental treatment options to restore patient function and appearance. However, numerous significant factors influence the predictability of survival or the success rates of dental implants, some of which, such as vitamin D levels, have not been included in many studies. The main purpose of this systematic review was to investigate whether there is a relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
5
0
2
Order By: Relevance
“…A high rate of vitamin D deficiency (VDD) is reported among AD individuals; for instance, a study from 2022 on five European cohorts, a total of 1028 patients with autoimmune AD, found that 34–57% of them had VDV, defined as a level of 25-hydroxyvitamin D (25OHD) between 10 and 20 ng/mL, while 5–22% had severe VDV (a value of 25OHD below 10 ng/mL) [ 140 ]. VDV impacts general oral health, especially in children, pregnant women, and seniors (where reports showed correlations with bone density); it is suggested to be an additional contributor to PD, and probably to dental implant failure [ 141 , 142 , 143 ]. VD replacement might help the process of osseous integration after dental implants, as its role in bone healing has been noted [ 144 , 145 ].…”
Section: Methodsmentioning
confidence: 99%
“…A high rate of vitamin D deficiency (VDD) is reported among AD individuals; for instance, a study from 2022 on five European cohorts, a total of 1028 patients with autoimmune AD, found that 34–57% of them had VDV, defined as a level of 25-hydroxyvitamin D (25OHD) between 10 and 20 ng/mL, while 5–22% had severe VDV (a value of 25OHD below 10 ng/mL) [ 140 ]. VDV impacts general oral health, especially in children, pregnant women, and seniors (where reports showed correlations with bone density); it is suggested to be an additional contributor to PD, and probably to dental implant failure [ 141 , 142 , 143 ]. VD replacement might help the process of osseous integration after dental implants, as its role in bone healing has been noted [ 144 , 145 ].…”
Section: Methodsmentioning
confidence: 99%
“…Durante la oseointegración el calcitriol afecta la activación y diferenciación de osteoblastos y osteoclastos, entonces la vitamina aumenta la mineralización ósea, también se ha descubierto que participa en la maduración y función las células óseas por su actividad precursora. 15 Por otra parte, una regeneración ósea es un procedimiento que comúnmente se puede llevar antes o durante la colocación de un implante y resultados de estudios in vitro indican que tiene un alto potencial terapéutico debido a que existe una mejoría en la diferenciación de células madre en los osteoblastos. 16 La dosis recomendada según el Instituto de Medicina de los EE.…”
Section: Factores Relacionados a La Deficiencia De Vitamina D Y La Os...unclassified
“…Moreover, a recent systematic review concluded that it is difficult to prove a direct relationship or causality between low serum vitamin D levels and early dental implant failures. The small number of clinical trials and their limited number of patients make it necessary to carry out future research to clarify the specific role of vitamin D deficiencies 402 . Conclusions from other systematic reviews were the opposite: serum vitamin D levels in patients may play a relevant role in osseointegration, marginal bone loss, and dental implant survival 403 …”
Section: Diet‐related Factors Altering Bone Metabolismmentioning
confidence: 99%